Faktor Yang Mempengaruhi Kejadian Kecelakaan Kerja pada Pekerja Pemanen Kelapa di Parit I Kelurahan Sungai Salak - Yoga Saputra Yoga; Bayu Azhar (HEALTH CARE : JURNAL KESEHATAN, 2022)
Abstract Harvesting activities have a risk of work accidents due to workers not complying with the use of facilities and infrastructure used when carrying out activities at work. The purpose of this study was to determine the factors that influence the incidence of work accidents on coconut harvesting workers in Parit I, Sungai Salak Village. This research is a quantitative research using a correlation research design that uses a Cross Sectional approach. The population in this study were all coconut harvesting workers in Parit 1 Sungai Salak Village, Tempuling District, Indragiri Hilir Regency, Riau, which amounted to 42 respondents. The data obtained were analyzed by univariate and bivariate. The results of this study found that 23 respondents (64.3%) who experienced work accidents, based on age as many as 24 respondents (57.1%) had a risk age of 34 years, based on years of service it was found that 26 respondents (61.9%) ) workers who are at risk 6 years, have high school education, namely 16 respondents (38.1%). do not use personal protective equipment while working, namely 37 respondents (88.1%). The results obtained are three factors that have no effect, including age, P value 0.347 > 0.05, working period factor, P value 0.746 > 0.05, personal protective equipment use factor P value 1,000 > 0.05, which means There is no correlation between the use of personal protective equipment and the incidence of work accidents. Kywords: Work Accident Incident, Coconut Harvester